Metafore del piacere. Tra Freud e Derrida - Feyles, Martino (Bollettino Filosofico, 2021)
In the first part of the article some of Freud’s texts are analyzed to show that: (1) Freud’s analysis of pleasure has an uncertain epistemological status, which lies between the fictional, the philosophical and the scientific; (2) in Beyond the Pleasure Principle the thesis on the nature of pleasure, despite its problematic epistemological legitimacy, takes on a metaphysical significance. In the second part of the article, the interpretation proposed by Derrida in Spéculer – sur “Freud” is analyzed to show that: (3a) Freud's analysis depends on a preliminary interpretation of the notion of pleasure that is not critically questioned; (3b) because of this preliminary assumption, Freudian language always remains metaphorical. Finally (4), starting from Spéculer – sur “Freud”, some general considerations on the relationship between psychoanalysis and deconstruction are proposed. Keywords: Deconstruction, Derrida, Freud, Pleasure, Psychoanalysis